Activity Community App : implementation of jobs and voluntary work portal for senior citizens on mobile platform (Android) - Kerk, Kok Hui (2016)
Ageing population has been a concern raised within our society in the recent years, where potential issues are foreseen, such as lacking of manpower or ageing workforce, and the increase in medical expenses. To minimize the impacts which will arise over the years, this project aims to research on ways to motivate senior citizens to continue working and participating in activities such as volunteer work to promote and adopt a healthy ageing lifestyle.